Low CETP activity and unique composition of large VLDL and small HDL in women giving birth to small-for-gestational age infants - Marie Cecilie Paasche Roland (Nature Portfolio, 2021)
Abstract Cholesteryl ester transfer protein (CETP) regulates high density lipoproteins (HDL)-cholesterol (C) and HDL-C is essential for fetal development. We hypothesized that women giving birth to large-for-gestational-age (LGA) and small-for-gestational age (SGA) infants differed in longitudinal changes in lipoproteins, CETP activity and HDL-C and that placentas from women with higher or lower circulating HDL-C displayed differential expression of mRNAs involved in cholesterol/nutrient transport, insulin signaling, inflammation/ extracellular matrix (ECM) remodeling. Circulating lipids and CETP activity was measured during pregnancy, NMR lipidomics in late pregnancy, and associations with LGA and SGA infants investigated. RNA sequencing was performed in 28 placentas according to higher and lower maternal HDL-C levels. Lipidomics revealed high triglycerides in large VLDL and lipids/cholesterol/cholesteryl esters in small HDL in women giving birth to SGA infants. Placentas from women with higher HDL-C had decreased levels of CETP expression which was associated with mRNAs involved in cholesterol/nutrient transport, insulin signaling and inflammation/ECM remodeling. Both placental and circulating CETP levels were associated with growth of the fetus. Low circulating CETP activity at 36–38 weeks was associated with giving birth to SGA infants. Our findings suggest a link between increased maternal HDL-C levels, low CETP levels both in circulation and placenta, and SGA infants.